Cyborgs dan Perempuan Menurut Pandangan Posthumanisme Donna J. Haraway - Bagas Dwika Putra; Radea Yuli Ahmad Hambali (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
There is a need to re-question the human condition today, and technology changes the history of human civilization and social development, so that the